ANALISIS PERAN KEPEMIMPINAN DALAM UPAYA MENINGKATKAN EFESIENSI ADMINISTRASI DI DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN NIAS UTARA - Notatema Harefa; Syah Abadi Mendrofa; Sukaaro Waruwu; Eliagus Telaumbanua (Jurnal Publikasi Manajemen Informatika, 2026)
This study examines the role of leadership in improving administrative efficiency at the Community and Village Empowerment Agency (DPMD) of North Nias Regency. The research is motivated by initial findings indicating issues related to administrative efficiency within the agency, such as a lack of active supervision from leaders, hindered inter-division coordination that can lead to duplicated work, and a slow adaptation to technology. Additionally, a lack of staff initiative in managing data and information was found to lower productivity. Therefore, this study aims to analyze how the leadership styles and practices implemented by leaders can be a solution to these challenges. The research uses a qualitative descriptive method. Data was collected through three main techniques: in-depth interviews, participatory observation, and documentation studies. The findings from interviews show that leaders at the DPMD of North Nias Regency have implemented various innovative strategies to enhance efficiency. These strategies include structured work plans with balanced task distribution, the use of data processing technology, and routine coordination meetings. Furthermore, leaders have shown a proactive attitude in motivating staff to take initiative, enabling them to make relevant decisions within their scope of duties without always waiting for orders. The study also found that the applied leadership style not only focuses on managerial aspects but also on building strong interpersonal relationships. Leaders were successful in creating a conducive work environment through open communication with staff, where every input and critique is heard constructively. Staff members feel valued and involved in the administrative decision-making process, which in turn fosters a sense of ownership and responsibility for their work. The implementation of task and authority delegation has also been a key to success. Leaders give full trust to staff to complete administrative tasks, which not only enhances their independence but also encourages individual skill development. This approach has significantly contributed to increased productivity and morale. In conclusion, the role of leadership at the Community and Village Empowerment Agency of North Nias Regency is proven to have a substantial impact on improving administrative efficiency. Effective leadership, characterized by clear direction, good communication, active participation, and the ability to delegate tasks and authority, can create a more structured and productive work culture. This study recommends that the DPMD of North Nias Regency continues to strengthen adaptive and participatory leadership strategies to face increasingly complex administrative challenges in the future, as well as integrating continuous leadership training for all levels of leadership.